2006
DOI: 10.1007/s10745-006-9021-5
|View full text |Cite
|
Sign up to set email alerts
|

Farmer Choice of Sorghum Varieties in Southern Mali

Abstract: In southern Mali and throughout the semiarid tropics, small-scale family farmers are faced with the challenge of producing adequate harvests in difficult biophysical and socioeconomic environments. Professional plant breeders have had much difficulty developing modern varieties that outperform farmers' traditional varieties in these environments, in part because of an incomplete understanding of why farmers choose the varieties they grow. Improved understanding of farmers' varietal choices can contribute to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 14 publications
4
46
0
3
Order By: Relevance
“…In contrast, to the maize variety 513 that may not survive beyond 5 months with lack of rains and susceptibility to frosts attacks. Many studies have shown that farmers have mixed long and short season crops systematically over years to cope with climatic variability [87][88][89]. Umande and Muhonia farmers confirm other studies that showed farmers prefer long cycle and short cycle varieties for a variety of reasons such as superior taste and high yields, tolerance to the drought conditions [4,87].…”
Section: Coping and Adapting To Climate Change And Variabilitymentioning
confidence: 57%
See 1 more Smart Citation
“…In contrast, to the maize variety 513 that may not survive beyond 5 months with lack of rains and susceptibility to frosts attacks. Many studies have shown that farmers have mixed long and short season crops systematically over years to cope with climatic variability [87][88][89]. Umande and Muhonia farmers confirm other studies that showed farmers prefer long cycle and short cycle varieties for a variety of reasons such as superior taste and high yields, tolerance to the drought conditions [4,87].…”
Section: Coping and Adapting To Climate Change And Variabilitymentioning
confidence: 57%
“…Many studies have shown that farmers have mixed long and short season crops systematically over years to cope with climatic variability [87][88][89]. Umande and Muhonia farmers confirm other studies that showed farmers prefer long cycle and short cycle varieties for a variety of reasons such as superior taste and high yields, tolerance to the drought conditions [4,87]. We argue that Umande and Muhonia prefer both long and short cycle crops to enable them to manage uncertainty of variable weather in terms of rainfalls, droughts and frosts.…”
Section: Coping and Adapting To Climate Change And Variabilitymentioning
confidence: 99%
“…It is a staple crop of semiarid sub-Saharan Africa. In West Africa, farmers grow mainly guinea race landraces that are especially adapted to the harsh and unpredictable conditions of the sub-Sahelian zone [4]. In West Africa, especially in Burkina Faso, it is the staple crop and produced in low-input cropping systems [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to have knowledge of farmer varietal choice, because it can help plant breeders and agricultural extension services to better serve the needs of farmers, as well as contribute to collaboration between farmers and plant breeders [10]. Farmer varietal choice is often based on the performance of different varieties in various environmental conditions [11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study of the adoption and impact of dual-purpose cowpea among farmers in semi-arid region of Nigeria, Abdullahi [13] found that cowpea farmers grow both short-cycle and long-cycle cowpea varieties. In a study of Malian farmers choice of traditional sorghum varieties in terms of one and more than one variety and short-cycle or long-cycle varieties, [10] found that farmers grow a combination of short-cycle and long-cycle varieties to optimize yield, yield stability and post-harvest traits, such as taste. In a review of farmer genetic resources Jarvis [14] and others found that farmers who have more wealth were more likely to cultivate more varieties than farmers who have less wealth.…”
Section: Introductionmentioning
confidence: 99%